Effect of deficit irrigation on soil CO2 and N2O emissions and winter wheat yield. (10th January 2021) - Zhong, Yuxuan; Li, Jianzhu; Xiong, Hao
Abstract: Determining the features of soil CO2 and N2 O emissions and the driving factors of deficit irrigation is of great significance for optimizing cropland management modes. In this study, the experimental plots were selected in a typical area of the North China Plain during the whole growth period of winter wheat. Six irrigation levels were designed to investigate the effect of deficit irrigation on CO2 and N2 O emissions and wheat yield. CK represents reference irrigation (full-water irrigation), and T1-T5 represent irrigation water decreasing by 10%, 20%, 30%, 40% and 50%, respectively. The experiment showed that soil CO2 and N2 O emissions decreased under the deficit irrigation treatments (T1, T2, T3, T4 and T5). Pearson correlation analysis showed that there were significant correlations between the CO2 emissions and soil temperature or water-filled pore space (WFPS) under the different irrigation treatments, and these correlations had a significant linear relationship. However, there was no discernible correlation between the N2 O emissions and soil temperature or WFPS under the other irrigation treatments except the CK treatment. Compared with that of the CK treatment, the equivalent CO2 of the T1-T5 treatments decreased by 8.6%, 5.7%, 14.3%, 14.1% and 19.3%, respectively. Compared with the CK treatment, the T3-T5 treatments significantly decreased the N2 O emissions (P < 0.05), and the reduction in CO2 by deficit irrigation did not reach a significant level (P > 0.05). Moreover, some deficit irrigation treatments had negative influences on the yield of winter wheat. Through the TOPSIS method and RSR method, the effects of the irrigation levels on equivalent CO2 and wheat yield were evaluated comprehensively. The T3 treatment was shown to be the best irrigation level for the conservation of wheat yield and reduction of greenhouse gas emissions. Therefore, the corresponding irrigation water amount under the T3 treatment could be regarded as the most appropriate scheme. Graphical abstract: Image 1 Highlights: Deficit irrigation (T1-T5) resulted in a decrease in CO2 and N2 O emissions. Soil temperature and moisture had a significant effect on CO2 emissions. Soil temperature and moisture had no impact on N2 O emissions. The most appropriate irrigation level was determined using two evaluation methods. Wheat yield and greenhouse gas emissions were considered in the evaluating process.